Analysis of the Linkages and Impact of Electricity Industry Investments on Leading Industries in East Nusa Tenggara Province - Barsua, Ni Putu Esti Utami; Parulian, Firman Emmanuel Declarantius; Wulandari, Yulia Nawang; Dilaga, I Made Joel Jaya; Kartiasih, Fitri (Eko-Regional: Jurnal Pembangunan Ekonomi Wilayah, 2026)
This study aims to identify key industries in East Nusa Tenggara (NTT) in 2023, examine the linkages between these industries, and analyze the impact of investment shocks in the electricity sectors. Using the updated 2023 input-output tables, the analysis includes interrelationships, multiplier effects, and impact simulations. The study reveals that investment in the electricity sector is vital for boosting production and distribution capacity in NTT. Eight important NTT industries demonstrated significant forward and backward links in 2023. It is anticipated that investments made in the electrical sector will increase total economic production. This investment benefits not just the electrical industry directly but also other industries, especially wholesale and retail trade. In the future, an exploration of the possibilities of renewable energy should be conducted.